Identification of risk in cutaneous melanoma patients: Prognostic and predictive markers. Issue 2 (12th December 2018) - Hyams, David M.; Cook, Robert W.; Buzaid, Antonio C.
Abstract : New therapeutic modalities for melanoma promise benefit in selected individuals. Efficacy appears greater in patients with lower tumor burden, suggesting an important role for risk‐stratified surveillance. Robust predictive markers might permit optimization of agent to patient, while low‐risk prognostic markers might guide more conservative management. This review evaluates protein, gene, and multiplexed marker panels that may contribute to better risk assessment and improved management of patients with cutaneous melanoma.